Project-based learning of native species for the phytoremediation of drained waters in the Tangana mine in the Huachocolpa District, Huancavelica (Peru) - Enríquez Donaires, Amadeo (2020)
The present research aims to evaluate the project-based learning of native species for the phytoremediation of drained waters in the Tangana mine and the bioaccumulation capacity of lead and cadmium through the species putacca (Family apiaceae) and cattail (Scirpus californicus), in the District of Huachocolpa of the Province and Department of Huancavelica (Peru). Applying the instrumental analytical methodology, satisfactory results were obtained for the environment, since both metals (cadmium and lead) were absorbed by these species. In this context, the following conclusions were obtained: a) The concentration of cadmium (Cd) and lead (Pb) in drained waters of the Tangana mine were 0.2661 mg Cd / l and 25.7220 mg Pb / l, the quantification of cadmium (Cd) and lead (Pb) concentration in the cattail species was 0.0007 mg Cd / Kg and 0.0037mg Pb / Kg, the quantification of the concentration of cadmium (Cd) and lead (Pb) in the putacca species was 0.0020 mg Cd / Kg and 0.0948 mg Pb / Kg). From the above it is inferred that putacca has a higher absorbance than cattail. b) Collaborative learning with the complement of ICTs allows students of different educational levels to reduce the gaps in access to information and interaction with experts in the field.